2018
DOI: 10.1002/jcpy.1068
|View full text |Cite
|
Sign up to set email alerts
|

Variety Seeking, Satiation, and Maximizing Enjoyment Over Time

Abstract: In this article, we examine the different ways in which consumers balance their consumption behavior in order to maximize utility. In particular, we focus on how people balance repeating the same options with the decision to seek variety. While earlier research represented variety seeking as a means of reducing physical satiation (McAlister, 1982), more recent research suggests that the relationship between choosing variety and minimizing satiation is more complex, as these behaviors may be motivated and influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 115 publications
1
64
1
Order By: Relevance
“…In SC context, to achieve variety, the vendor needs to consistently disclose various products and services through varying experience using text, image or video, embedded and exposed in the social interaction (Church and Salam, 2010). Specifically, the diversity of content, products and services can be achieved by modifying specific attribute, as well as through rebranding and repackaging their content and product (Sevilla and Kahn, 2018; Kim et al , 2018). Therefore, by maintaining the continuity of content and experience which is fresh and varied, users tend to refrain from satiation and enjoy interaction which is likely to help in reducing intention to switch to other sites, especially for people with high experience of SC usage, according to moderating factor analysis result.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…In SC context, to achieve variety, the vendor needs to consistently disclose various products and services through varying experience using text, image or video, embedded and exposed in the social interaction (Church and Salam, 2010). Specifically, the diversity of content, products and services can be achieved by modifying specific attribute, as well as through rebranding and repackaging their content and product (Sevilla and Kahn, 2018; Kim et al , 2018). Therefore, by maintaining the continuity of content and experience which is fresh and varied, users tend to refrain from satiation and enjoy interaction which is likely to help in reducing intention to switch to other sites, especially for people with high experience of SC usage, according to moderating factor analysis result.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Previous research also provides theoretical explanations and boundary conditions for variety-seeking. First, variety-seeking is one way to reduce satiation (McAlister, 1982; Sevilla et al, 2019). Satiation may involve the choice outcome as well as the choice process.…”
Section: Literature Review and Main Predictionsmentioning
confidence: 99%
“…On the other hand, when the decision involves choosing options from the same brand (typically, choosing between multiple flavor options from the same brand), freedom of choice is not salient, but the preference for different flavors is expected to be high. To support this argument, Inman (2001) found that flavor-based variety was strongly related to sensory-specific satiation, which is closely related to preference rather than freedom-seeking (see McAlister, 1982; Sevilla et al, 2019). In addition, Huang and Wyer (2015) also suggested that concrete (vs. abstract) construals lead to low variety-seeking.…”
Section: Literature Review and Main Predictionsmentioning
confidence: 99%
“…), those based on experiences perceived through the senses are likely to trigger consumer sensory adaptation, even satiation (Larson et al, 2013). Sevilla et al (2019) explain that when consumers anticipate satiation will occur, they may choose to seek variety as a proactive behaviour to delay satiation. Therefore, their intention to seek and try other retailers, who might provide them with new and different experiences, also grows.…”
Section: Introductionmentioning
confidence: 99%